2011
DOI: 10.1063/1.3554256
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of patterned Co/Pd multilayers with graded magnetic anisotropy

Abstract: Magnetization reversal and the effect of patterning have been investigated in full-film and dot arrays of Co/Pd multilayers, using the first-order reversal curve and scanning electron microscopy with polarization analysis techniques. The effect of patterning is most pronounced in low sputtering pressure films, where the size of contiguous domains is larger than the dot size. Upon patterning, each dot must have its own domain nucleation site and domain propagation is limited within the dot. In graded anisotropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…,19,27 At low Ar pressures, the sputtered atoms Author to whom correspondence should be addressed. Electronic mail: kailiu@ucdavis.edu.…”
mentioning
confidence: 99%
“…,19,27 At low Ar pressures, the sputtered atoms Author to whom correspondence should be addressed. Electronic mail: kailiu@ucdavis.edu.…”
mentioning
confidence: 99%
“…domain, exchange decoupled system, but with electrically connected magnetic entities [50]. Furthermore, similar suppression of domain motion has been reported in 1.4μm circular dot arrays of graded Co/Pd multilayers [212]. Interestingly it was shown that domains continue to exist within each Co/Pd dot.…”
Section: Magnetic Properties Of Continuous Co/pt Multilayerssupporting
confidence: 68%
“…7 The interlayer dipole interactions are ferromagnetic, causing a reduction in the switching field, however for 3 lm elements we only expect a decrease of the order of $10 Oe (calculated by the macrospin approximation on square structures 15 with M s ¼ 1.3 Â10 3 emu/cm 3 , magnetic layer thickness of 0.75 nm and the average distance between magnetic layers of 2.14 nm in our stack.). In general, patterning the film to the element sizes in the range studied here leads to increases in H c , 12,13,16 whilst the strength of the interlayer couplings is likely to decrease due to edge effects. 12,17,18 However, within the errors of the measurement, H c and interlayer coupling remain constant as a function of size in this study.…”
mentioning
confidence: 90%